Implikasi Hukum Bisnis Terhadap Perlindungan Konsumen dalam Transaksi E-Commerce di Indonesia - Sarah Simanjuntak; Dina Oviani Siregar; Listra Debora Siahaan; Toman Sony Tambunan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the implications of business law on consumer protection in e-commerce transactions in Indonesia. The results of the study indicate that business law plays an important role in protecting consumers in e-commerce transactions. However, the effectiveness of existing laws and regulations is still questionable because there are still many cases of fraud and unfair business practices. Therefore, this study suggests the need for improvements to laws and regulations, increased consumer awareness, effective supervision, and cooperation between the government and business actors to improve consumer protection in e-commerce transactions in Indonesia.